Dual-task training and cognitive performance in individuals with coronary artery disease and/or heart failure: a systematic review - Cezareti, Talita; Souza, Wallace Machado Magalhães de; Deslandes, Andrea Camaz; Guimarães, Tereza Cristina Felippe; Kasal, Daniel Arthur Barata; Rodrigues Junior, Luiz Fernando; Mediano, Mauro Felippe Felix (Frontiers in Cardiovascular Medicine, 2025)
IntroductionDual-task training (DTT) emerged as a promising intervention strategy to improve cognition in individuals with cardiovascular diseases (CVDs). The aim of this study is to describe the literature on the relationship between motor-cognitive DTT and cognitive performance (CP) in individuals with coronary artery disease (CAD) and/or heart failure (HF).MethodThis systematic review includes intervention and observational studies that assessed motor-cognitive DTT on CP in individuals with CAD and/or HF. Searches were performed in the MEDLINE/Pubmed, Scielo, Lilacs, PEDro, and EMBASE databases. Methodological quality was assessed using the PEDro and ROBII scales for intervention studies and the Newcastle-Ottawa Scale for observational studies. The certainty of evidence was assessed using Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach.ResultsA total of 2,098 articles were retrieved, and 21 articles were selected for full reading. Among these, 16 were excluded according to pre-specified exclusion criteria, resulting in five studies conducted between 2018 and 2022, conducted in three countries (United States, Portugal, and Russia). The studies included 228 individuals, comprising one study with HF participants, one including women with CAD, two including individuals that underwent myocardial revascularization, and one with patients with CAD enrolled in a phase 2 of cardiac rehabilitation program. Each study used different combinations of motor and cognitive tasks, conducted sequentially (n = 2 studies) or simultaneously (n = 3 studies), with one study using virtual training. The overall certainty of evidence for CP was low according to GRADE approach. Reduction in postoperative cognitive dysfunction after myocardial revascularization was observed in two studies. Moreover, the results indicate that DTT may have a positive impact on memory, selective attention, and conflict resolution capacity.ConclusionThe studies reviewed indicate motor-cognitive DTT as a potential approach to improve CP in individuals with CAD and/or HF.Systematic Review Registrationwww.crd.york.ac.uk/prospero/display_record.php?ID=CRD4202341516, identifier (CRD 4202341516).